Addressing the Challenges in Federating Edge Resources - Baktir, Ahmet Cihat; Sonmez, Cagatay; Ersoy, Cem; Ozgovde, Atay; Varghese, Blesson (Fog and Edge Computing, 2019)
This chapter discusses two key challenges: networking and management in federating edge deployments. Additionally, it considers resource and modeling challenges that will need to be addressed for a federated edge. The chapter discusses potential avenues for resolving the networking challenges. Throughout the chapter, the general term edge refers to a collection of technologies that aim toward decentralizing data center resources for bringing computational resources closer to the end user. The chapter discusses the principles of mobile cloud computing (MCC), cloudlets, fog computing, and multi‐access edge computing (MEC). Federating edge resources brings about a larger number of networking challenges related to scalability. The prospect of including an edge layer between cloud data centers and user devices for emerging applications is appealing because latency and transmission of data to the core of the network can be minimized to improve the overall quality of service (QoS) of an application.